Brainlesion : glioma, multiple sclerosis, stroke and traumatic brain injuries : second International Workshop, BrainLes 2016, with the challenges on BRATS, ISLES and mTOP 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, Revised selected papers /: glioma, multiple sclerosis, stroke and traumatic brain injuries : second International Workshop, BrainLes 2016, with the challenges on BRATS, ISLES and mTOP 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, Revised selected papers. (2016) - Unknown
No abstract available